2022
DOI: 10.25133/jpssv302022.025
|View full text |Cite
|
Sign up to set email alerts
|

Poverty Dynamics in Indonesia: The Prevalence and Causes of Chronic Poverty

Abstract: This study aims to determine the chronicity of poverty in Indonesia using the equally distributed equivalent (EDE) poverty gap method, tracking Indonesian households in 2007 and 2014. The results indicate that the largest component of poverty among households was chronic (77%). Compared to transient poverty, chronic poverty is more common across individuals. Unlike previous studies, we used data at the district level to measure the poverty line, discovering that the cost of poverty inequality is lower than oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
(84 reference statements)
0
6
0
1
Order By: Relevance
“…Third, the creation of new police units and reorganization of police forces (Nurmandi et al 2016) might result in a more effective police institution. Fourth, social programs and government aid have increased (Sugiharti et al 2022) in the form of cash transfers, food aid, social health system, energy subsidies, among others, which may help reduce crime. Still, evidence on the effects of individual and community aid on crime remains mixed (Cameron and Shah 2014).…”
Section: Crime In Indonesia; Backgroundmentioning
confidence: 99%
“…Third, the creation of new police units and reorganization of police forces (Nurmandi et al 2016) might result in a more effective police institution. Fourth, social programs and government aid have increased (Sugiharti et al 2022) in the form of cash transfers, food aid, social health system, energy subsidies, among others, which may help reduce crime. Still, evidence on the effects of individual and community aid on crime remains mixed (Cameron and Shah 2014).…”
Section: Crime In Indonesia; Backgroundmentioning
confidence: 99%
“…Poverty remains a prevalent problem in Indonesia, so government policies and strategies have always prioritized its alleviation Sugiharti et al 2022b). Figure 2 shows that provinces with a high percentage of poverty also display high crime rates.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, these dwellers cannot escape poverty to access conducive housing as their current job does not offer them a high enough income. Their average household income will only lead them to chronic poverty, as a study in Indonesia illustrated that housing is less accessible to impoverished people (Sugiharti et al, 2022). Findings also revealed that most informants from the urban squatters in Sentul claimed they could not afford proper housing because their household income was less than MYR 4,850 (USD 1.044) per month, deemed a low-income household or the B40 category.…”
Section: Discussionmentioning
confidence: 99%